The Relationship of Arginine Deprivation, Argininosuccinate Synthetase and Cell Death in Melanoma - Niramol Savaraj; Chunjing Wu; Marcus Tien Kuo; Min You; Medhi Wangpaichitr; Carlos Robles; Seth Spector; Lynn Feun (AboutScience Srl, 2007)
It has been shown that melanoma cells do not express argininosuccinate synthetase (ASS) and therefore are unable to synthesize arginine from citrulline. Depleting arginine using pegylated arginine deiminase (ADI-PEG20) results in cell death in melanoma but not normal cells. This concept was translated into clinical trial and responses were seen. However, induction of ASS expression does occur which results in resistance to ADI -PEG20. We have used 4 melanoma cell lines to study factors which may govern ASS expression. Although these 4 melanoma cell lines do not express ASS protein or mRNA as detected by both immunoblot and northernblot analysis, ASS protein can be induced after these cells are grown in the presence of ADI-PEG20, but again repressed after replenishing arginine in the media. The levels of induction are different and one cell line could not be induced. Interestingly, a melanoma cell line with the highest level of induction could also be made resistant to ADI-PEG20. This resistant line possesses high levels of ASS mRNA and protein expression which cannot be repressed with arginine. Our study indicates that ASS expression in melanoma cells is complex and governed by biochemical parameters which are different among melanoma cells.